Liquefaction of palm kernel shell to bio-oil using sub- and supercritical water: An overall kinetic study - Chan, Y.H. (Elsevier B.V., 2018)
Palm kernel shell was liquefied using sub- and supercritical water at 330â390 Â°C and 25 MPa for different reaction times. The overall kinetics of the liquefaction based on the conversion of biomass was analyzed using kinetic equation adopted from the literature, and the kinetic parameters were estimated from the evaluation of the kinetic equation. In this study, the rate constant (k) increased from 0.43 to 0.49 sâ1 with reaction temperature from 330 to 390 Â°C. The relationship of rate constant (k) and temperature agreed reasonably well with the Arrhenius equation. The activation energy (E) and pre-exponential factor (A) values for the liquefaction process were estimated to be 6.70 kJ/mol and 1.65 sâ1, respectively. In addition, the experimental bio-oil yields with respect to reaction time were well-fitted using the modified Reverchon-Sesti Osseo equation. Â© 2018 Energy Institute